Striving for Survival and Success in play The Flick (2013) by Annie Baker - Gina Felandri; Desvalini Anwar (Universitas Negeri Padang, 2019)
This thesis is the analysis of a play written by Annie Baker entitled The Flick (2013). It explores the issue of striving for survival and success reflected by the main character. This issue refers to the way the main character deals with all the difficulties and tries to reach a dream in his life. It is also intended to find out the contribution of fictional devices such as character, plot (conflict), and stage direction in revealing the issue of striving for survival and success. This analysis is related to the concept of life instinct which developed by Sigmund Freud and also supported by the text-based and context-based interpretation. The result of this analysis shows about the way the main character persistence in surviving and achieving goals in his life through the efforts of socialization and self-interest exploration made by the character.